International spillovers and employment in a disequilibrium macroeconomic model for Germany - Wolfgang Franz; Gustav W. Heidbrink (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
This paper gives a short overview of the unemployment problem in Germany during the last decade. In a disequilibrium macroeconomic framework there are strong linkages between spillovers of domestic demand on trade flows and labor demand. In the econometric part of the paper these linkages are estimated. For the determination of spillovers special emphasis is put on the trade flows between Germany and a group of four main EEC trading partners. It follows a discussion of employment and labor demand series for Germany and the group of EEC countries with some remarks on possible macroeconomic causes of the German unemployment problem.
Keywords: 330; Arbeitslosigkeit; Makroökonomik; Neukeynesianische Makroökonomik; Deutschland